2016
DOI: 10.1159/000445808
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Therapeutic Efficacy and Urodynamic Findings of Solifenacin Succinate versus Mirabegron in Women with Overactive Bladder Syndrome: Results of a Randomized Controlled Study

Abstract: Introduction: We assessed clinical and urodynamic effects of solifenacin versus mirabegron in women with overactive bladder (OAB) syndrome. Material and Methods: Eighty women with OAB were randomized into 2 groups. In group A, the patients received solifenacin 5 mg once a day for 12 weeks; in group B, the patients received mirabegron 50 mg once a day for 12 weeks. Symptoms were assessed with OAB Symptom Score (OABSS). Patients underwent urodynamic investigation with pressure flow study. OABSS and urodynamic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In addition, three studies were excluded because they had been published in a different periodical. Finally, five articles containing five RCTs were included in our study to analyze mirabegron and solifenacin monotherapy for OAB treatment. The baseline characteristics of these five studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, three studies were excluded because they had been published in a different periodical. Finally, five articles containing five RCTs were included in our study to analyze mirabegron and solifenacin monotherapy for OAB treatment. The baseline characteristics of these five studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The sample capacity was calculated (Table ). Scaldazza et al is not a double‐blinded design, so that the grade of the blinding method was “B,” and each of the other studies was grated as “A.”…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The urodynamic effects of antimuscarinic agents in OAB and NLUTD have been well documented in previous studies [26], but the clinical experience and evidence of mirabegron efficacy as demonstrated by UDS are still inadequate. Matsukawa et al [27] and Vecchioli Scaldazza and Morosetti [28] reported a significant increase in cystometric capacity by an average of 37 mL and 41 mL, respectively, in women with OAB who received mirabegron 50 mg once a day for 12 weeks. In a study involving men with OAB, mirabegron add-on therapy with tamsulosin significantly increased cystometric capacity (by 24%, from 170 to 212 mL) [29].…”
Section: Discussionmentioning
confidence: 99%